2020
DOI: 10.3390/su12030815
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Trade, FDI and the Upgrading of Regional Industrial Structure in China: Based on Spatial Econometric Model

Abstract: The upgrading of industrial structure is the core means of coordinating economic development and environment protection. Its spatial agglomeration can also reduce environmental pollution partly. The upgrading of China’s industrial structure has become an important issue concerned by the whole society. To better understand this issue, based on the provincial data of China (1997–2017), this paper strives to explore the spatial effects of foreign trade and foreign direct investment (FDI) on the upgrading of China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Industrial structure upgrading is a critical factor in achieving sustainable development goals in a country and globally (Zhang and Chen, 2018;Wang et al, 2020;Zheng J. et al, 2021;Wang and Li, 2022). As the second-largest economy in the world, China is shifting its development strategy from high speed to high quality, urgently searching for solutions to industrial structure upgrading.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial structure upgrading is a critical factor in achieving sustainable development goals in a country and globally (Zhang and Chen, 2018;Wang et al, 2020;Zheng J. et al, 2021;Wang and Li, 2022). As the second-largest economy in the world, China is shifting its development strategy from high speed to high quality, urgently searching for solutions to industrial structure upgrading.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the coefficients of lnfdi and growth become significantly positive; this finding may imply that the dynamic GMM estimation reveals a different pattern compared to the fixed effects model after further dealing with the issue of endogeneity caused by simultaneity. Following this line of thought, the proportion of foreign direct investment in a province increases and the labor productivity of tertiary industries in a province may also increase correspondingly, indicating that the higher a region’s degree of opening up to the outside world, the more favorable it is for upgrading the industrial structure (Wang et al, 2020). As the degree of opening up to the outside world increases, the degree of interaction between domestic and overseas industries increases, the market’s grasp of the global industry’s development direction is more accurate, and the demand for advanced emerging industries is strengthened.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…From the perspective of scientific and technological innovation heterogeneity, scholars divided innovation into technological innovation and product innovation, and found that technological innovation and product innovation promote economic growth through industrial structure upgrading via the mediating effect model [ 18 ]. In addition, other scholars, by analyzing the experience of science and technology innovation to promote industrial structure upgrading, found that government policy intervention has limitations, which can stimulate the rapid development of supported industries in the short term, but at the same time, it can also trigger the problem of homogeneous investment and construction overheating, leading to technological convergence [ 19 , 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%